Feasibility and Technical Reliability Study of a Standalone Rooftop Solar Power Plant System Using Python Pvlib: A Case Study on Renewable Energy Engineering Laboratory Building of Universitas Malikussaleh - Shaki S. Putra; Hermin Kartika Sari; Thomas Oka Pratama; Reza Putra (Politeknik Negeri Lhokseumawe, 2026)
This study evaluates the technical feasibility and reliability limits of a standalone rooftop solar power plant system for the Renewable Energy Laboratory at Universitas Malikussaleh, North Aceh. Utilizing the pvlib Python library and NASA POWER meteorological data from 2022 to 2024, a high-resolution time series simulation was conducted to model energy yield, battery dynamics, and Loss of Power Supply Probability (LPSP). The results reveal a significant seasonal reliability gap, while the system achieves optimal performance in dry months with LPSP 1%, it suffers critical power failures during the monsoon season, with LPSP peaking at 31.80% in December due to consecutive low irradiance days. Furthermore, the energy balance analysis highlights a system inefficiency where substantial energy curtailment occurs during high-irradiance periods despite severe deficits in wet months. Consequently, a pure off-grid configuration is deemed technically unfeasible for critical laboratory loads without unrealistic oversizing. The study concludes that transitioning to a PV-Hybrid topology with backup generation is essential to ensure operational continuity while complying with current non-export regulatory constraints.